EU Government bonds and banks: Home bias pervasive throughout member states but capital requirements differ greatly - Dominik Meyland; Dorothea Schäfer (DIW Weekly Report, 2018)
The current banking regulatory framework assigns EU government bonds a risk weight of zero. Since the European debt crisis, there has been increasing controversy over eliminating this equity capital privilege, which is viewed as contributing to the close relationship between state and bank risks. This report analyses the development of home bias-the tendency of major European banks to invest disproportionately high in domestic government bonds-for Germany, France, the United Kingdom, Italy, and Spain. In addition, it examines how much additional equity capital the banks of the euro area's major nations would require if equity capital privilege were eliminated. This report shows that home bias has increased over the last four years for many major European banks. Home bias only affects the additional capital requirements of Italian and Spanish banks, as their home countries have comparatively weak ratings. The estimated additional capital required if equity capital privilege were to be abolished indicates that Italian banks have the highest capital requirement at 11.5 billion euros, followed by the Spanish banks at 9.5 billion euros. Eliminating equity capital privilege would thus make it much more difficult to finance sovereign debt in Italy and Spain. Therefore, it would be advisable to introduce risk weighting for government bonds only after the EU sovereign debt levels have stabilized. At the same time, measures should be taken to make it easier for banks to reduce their home bias and better diversify their government bond portfolios.
Keywords: G20; G28; G01; 330; bank capital regulation; sovereign bonds